Effects of Cross-Country Skiing and Volleyball Training Characteristics on Some Respiratory Parameters in Female Athletes - Bilici, M. F.; Çelik, M.; Balica, D.; Bilici, Ö. F. (Journal of Education and Recreation Patterns, 2026)
This study aimed to examine the effects of sport-specific training on selected respiratory parameters in female cross-country skiers and volleyball players. A total of 36 women voluntarily participated in the study, including 12 cross-country skiers (age: 19.17 ± 1.11 years), 12 volleyball players (age: 20.42 ± 2.19 years), and 12 sedentary controls (age: 20.42 ± 2.27 years). Pulmonary function values were measured using a spirometer under standardized conditions. Statistical analyses were conducted using SPSS v30. Since the data showed a normal distribution, a one-way ANOVA was applied to compare mean respiratory parameters among groups, followed by Tukey`s post-hoc test for pairwise comparisons.